Awareness and Effects of Extension Services on the Adopt-A-Day Care School Program - Jocelyn S. De Vera (PT FORMOSA CENDEKIA GLOBAL, 2023)
One of the primary programs of an academic institution is to come out change by enabling people in certain communities by way of Extension Services. This study assessed the Awareness and Effect of Extension Services on the Adopt-A-Day Care School Program of the College of Teacher Education particularly the Bachelor of Elementary Education Program to the pupils of Bolaney Child Development Center in Bolaney,Alaminos City,Pangasinan, Philippines. The evaluation type of research intends to gain an understanding of the success and challenges that the implementer of the Adopt-A Day Care School Programs faced so as to guide future activities. A total of 56 respondents particularly mothers, guardians, daycare worker, elementary teachers, and barangay officers were utilized as respondents. Frequency counts ,percentages and weighted mean were used as statistical tools. Results showed that extension activities such as providing big books, pop-up books, and providing instructional materials enhance knowledge and skills to the children of the development center. School plays and puppet shows which was conducted in partnership with the Office of the Vice-mayor and City Library of Alaminos City and other officials boosted the confidence and alertness of the children. Meanwhile, the outreach programs, activities conducted by the NGO’s partners during school opening and Christmas seasons were highly appreciated by the respondents.